MECHANISMS OF SYSTEMIC INFLAMMATORY RESPONSE IN CARDIAC SURGERY (Modern education and development, 2025)
Recent data show that artificial circulation, myocardial and pulmonary ischemia-reperfusion, contact activation of leukocytes, anticoagulation, artificial ventilation, surgical trauma and other factors are powerful triggers of the inflammatory response after cardiac surgery. The combination of these factors leads to uncontrolled synthesis of various pro- and anti-inflammatory mediators, which in turn directly or indirectly cause dysfunction of endothelial cells, increased vascular permeability and manifestation of systemic inflammatory response syndrome with the development of organ dysfunction. The purpose of this literature review is to consider and systematize the main causes of the systemic inflammatory response after cardiac surgery with artificial circulation.